Walsh, Greg. Floor plan of the Walsh shed. - Nichter, Klara; Morrison, Adrian; LaDuke, John (2013)
Contemporary floor plan of the Walsh stage in Quidi Vidi Harbour. Measurements and floor plan completed by Nichter for the Quidi Vidi Field School 2013.